Psikologi Sastra dalam Novel Arafat Rahasia Besar Bocah Gaza Karya Arum Faiza - Indah Sari, Cici; Andriyani, Noni (J-LELC: Journal of Language Education, Linguistics, and Culture, 2023)
This research is focused on the field of literary psychology which discusses personality structure according to Freud, namely id, ego, and superego. The purpose of this study is to describe, analyze, interpret, and conclude the character's personality structure related to id, ego, and superego in Arafat's novel The Great Secret of the Gaza Boy by Arum Faiza. This research belongs to the type of qualitative research with descriptive methods (content analysis). The data in this study are quotes of words, phrases, clauses, and sentences that contain personality structures, namely id, ego, and superego contained in Arafat's novel The Great Secret of the Gaza Boy by Arum Faiza. From the results of research on the personality structure of the id, ego, and superego, the dominant element is the ego. Ego personality structure found as many as 20 data. The personality structure of the ego is more dominant because in Arafat's novel The Big Secret of the Gaza Boy tells of heroism. Because of the heroic theme of the novel, what appears the most is the ego personality structure. When talking about heroism, it must be real or real action. To support this, the author makes the characters appear more real in the novel. To show the heroic side can not be from id. Because to show the heroic side you have to look real, therefore you have to appear with ego.